2021
DOI: 10.3389/fcell.2021.736350
|View full text |Cite
|
Sign up to set email alerts
|

Gambogenic Acid Induces Endoplasmic Reticulum Stress in Colorectal Cancer via the Aurora A Pathway

Abstract: Colorectal cancer (CRC) is one of the most common malignancies in the world and has a poor prognosis. In the present research, gambogenic acid (GNA), isolated from the traditional Chinese medicine gamboge, markedly induced apoptosis and inhibited the proliferation of CRC in vitro and in vivo. Furthermore, GNA triggered endoplasmic reticulum (ER) stress, which subsequently activated inositol-requiring enzyme (IRE) 1α and the eukaryotic translation initiation factor (eIF) 2α pathway. Pretreatment with salubrinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Our results have shown that GNA significantly inhibited the proliferation of CRC in vitro and in vivo. In our previous studies, it has been confirmed that ER stress induced by GNA is closely related to CRC proliferation (Liu et al, 2021). Previous studies revealed that miR-1291 has antiproliferative functions in cancer cells (Chen et al, 2020), and it plays an important role in ER stress (Maurel et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Our results have shown that GNA significantly inhibited the proliferation of CRC in vitro and in vivo. In our previous studies, it has been confirmed that ER stress induced by GNA is closely related to CRC proliferation (Liu et al, 2021). Previous studies revealed that miR-1291 has antiproliferative functions in cancer cells (Chen et al, 2020), and it plays an important role in ER stress (Maurel et al, 2013).…”
Section: Discussionmentioning
confidence: 81%
“…In our previous studies, we found that GNA induced ER stress in CRC cells to inhibit proliferation (Liu et al, 2021) and miR‐1291 plays a role in ER stress of hepatoma cells (Maurel et al, 2013). Recently, by upregulated miR‐1291 in HCT116 and HT29 cells (Figure 2a), wefound that miR‐1291 could inhibit the proliferation of CRC cells (Figure 2b,c), which was consistent with previously report (Wang, Yokoyama, et al, 2022).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…[ 20 ] One study showed that gambogenic acid induces apoptosis and inhibits cell proliferation in HCT116 colon cancer cells by promoting the phosphorylation of eIF2α, IRE1α-XBP1s and PERK pathways through Aurora A. [ 21 ] In addition, another study found that a purified resin glycoside fraction from pharbitidis semen promote apoptosis in HT-29 and HCT-116 cells via ER stress. [ 22 ]…”
Section: Tumor Cell Proliferationmentioning
confidence: 99%
“…Head and neck cancer 1 Glaucocalyxin A ATF4/ CHOP/CHAC1 pathways [9] 2 Tetrandrine GRP78 and GADD153 [10] Digestive tract tumor 3 Tanshinone IIA BIP and CHOP [11] 4 Wogonoside IRE1α-TRAF2-ASK1 pathways [12] 5 Cyperus amuricus GRP78/BiP; CHOP-URP-PERK/IRE1/ATF6 [13] 6 Muscone PERK/ATF4/DDIT3 pathways [14] 7 Celastrol IRE1α-XBP1s pathways; GRP78/BiP, ATF4 and CHOP [15] 8 Salidroside p-PERK, p-eIF2a, ATF-6 and CHOP [16] 9 TTF1-NPs GRP78, PERK, IRE1α, ATF6 and CHOP; PERK-eIF2α-ATF4 and ATF6 [17,18] 10 Epigallocatechin-3-gallate p-PERK and p-eIF2α [19] 11 Shikonin PERK/elF2α/ATF4/CHOP, and IRE1α/JNK [20] 12 Gambogenic acid IRE1α, BiP, p-eIF2α, and ATF4 [21] 13 A purified resin glycoside fraction from pharbitidis semen ERS-JNK pathways [22] Gynecologic urogenital tumors 14 Saikosaponin-A GPR78 and CHOP [23] 15 Identification of dihydrotanshinone I PERK [24] Non-small cell lung cancer 16 Kushenol Z CHOP [25] 17 Evodiamine IRE1α-TRAF2-ASK1-JNK [26] 18 flavonoid components in Astragali Radix IRE1α-XBP1s [27] Others 19 Shikonin p-eIF2α and CHOP [28] 20 Psoralen CHOP, IREa, XBP-1s, GRP78, PERK and ATF-6 [29] 21 Artesunate ATF4-CHOP-CHAC1 [30] 22 (-)-Epigallocatechin-3-gallate GRP78, ATF4, XBP1s, CHOP and EDEM [31] 23 Asperuloside GRP78, p-PERK, p-eIF2α, CHOP, p-IRE1, XBP1, and ATF6 [32] Tumor cell autophagy Non-small cell lung cancer 24 Ginsenoside ATF4-CHOP-AKT1-mTOR [36] 25 Guangsangon E (GSE) ROS-ERS (GRP78, IRE1α and ATF4) [37] Colorectal cancer 26 Serpentine GRP78, p -PERK, p-elF2α and CHOP [38] 27 Cryptotanshinone Cell autophagy by ERS [39] Gynecologic urogenital tumors 28 Cucurbitacin-I IRE1α-caspase 1-p-PERK-eIF2-ATF4-CHOP [40] Tumor cell invasion and metastasis…”
Section: Tumor Cell Proliferationmentioning
confidence: 99%